Effectiveness of music intervention on cognitive function and neuropsychiatric symptoms in the elderly with dementia: a meta-analysis - Cecilia Wong TT (Frontiers of Nursing, 2022)
Dementia is increasing dramatically with an increasing elderly population. Pharmacological interventions are proven to have limited efficacy to treat many of the features of dementia. In such a situation, non-pharmacological means become important to help people with dementia, especially music therapy. The efficacy of music intervention on cognition has been barely explored in the literature, and the few studies that are available present inconsistent results. The aim of this systematic review is to have a meta-analysis on the effect of music therapy for improvements in cognitive functions as well as neuropsychiatric symptoms in the elderly with dementia.